Transformational Leadership, Competence, and Self-Efficacy in Influencing Elementary School Teachers' Performance - Imas Masriah (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research aims to investigate how primary school teachers' levels of transformational leadership, competency, and self-efficacy are related to student achievement. This study used a quantitative approach, and SPSS was used to analyse the collected data. In order to collect this information, 210 primary school teachers in Tangerang were picked at random and sent online questionnaires. The results of this study show that there is a positive relationship between transformational leadership and teacher performance, as well as a favourable relationship between transformational leadership, competency, self-efficacy, and teacher performance.